(untitled) - Kuo, Benjamin C. (Englewood Cliffs, N.J., 1967)
1. Introduction and mathematical preliminaries, 2. Tranfer function and graphical descriptions of linear systems, 3. State variable characterization of linear systems,...
Keywords: Automatic control,Điều khiển tự động